Analysis of the ways of working of learners in the final grade 12 mathematical literacy examination papers: focussing on questions related to measurement - Simons, Marius (University of Western Cape, 2014)
Magister Educationis - MEd === Mathematical Literacy has a dual meaning in South Africa. On the one hand it alludes to an understanding of the role of Mathematics in the real world. On the other hand it refers to a subject that is taken by students who generally do not do well in Mathematics and who do not wish to do a pure Mathematics course, This research focuses on the identification and investigation of errors, misconceptions and alternative ways of working in the responses of students in the final grade 12 Mathematical Literacy examination. The aim was to identify the errors, misconceptions and alternative ways of working and to discuss possible reasons for these errors and misconceptions. This aim was governed by the principle that feedback to students and teachers form a vital component in the teaching and learning process. This analysis only focused questions pertaining measurement in Mathematical Literacy. An analytical framework was constructed based on common errors and misconceptions identified by various researchers’ in the field of Mathematics. This analytical framework was used to classify and analyse the errors, misconceptions and alternative ways of working in Mathematical Literacy. The analysis was done using document analysis on a randomly selected sample of Mathematical Literacy scripts taken from across all education districts in the Western Cape. Great care was taken to prevent bias and cross checking was done by peers to ensure that the categories of errors were agreed on. The results of the analysis revealed that the errors identified for Mathematics are common to those of Mathematical Literacy. The findings in this project suggest that the analysis and feedback of errors and misconceptions may help to improve teaching and learning in Mathematical Literacy.